Musyawarah Dalam Penentuan Ganti Kerugian Bagi Pelaksanaan Pembangunan Untuk Kepentingan Umum - Tri Susilaningsih (University of Merdeka Malang, 2018)
Land acquisition is an activity to provide land for development in the public interest. The implementation of land acquisition is carried out based on Law Number 2 of 2012 concerning the Procurement of Land for Development in the Public Interest and related provisions governing it. This law was made to improve the welfare and prosperity of the nation, the State and society still guarantee the legal interests of the Entitled Party. The regulation of land acquisition in the law is correct but in terms of substance, this strategic and broad-impact law leaves a few records. So this Law which was passed on January 14, 2012 also cannot guarantee the acquisition of land for development. According to the conception of national land law, in principle land acquisition / land acquisition is carried out by means of deliberations between government agencies that require land with entitled parties, in terms of determining the location, form and / or amount of compensation. But there are times when deliberation is not reached or fails.How to cite item: Susilaningsih, T. (2018). Musyawarah Dalam Penentuan Ganti Kerugian Bagi Pelaksanaan Pembangunan Untuk Kepentingan Umum. Jurnal Cakrawala Hukum, 9(2), 214-224. doi:https://doi.org/10.26905/idjch.v9i2.2770